ANALISIS KINERJA REKSA DANA SAHAM DENGAN MENGGUNAKAN METODA RAW RETURN, SHARPE, TREYNOR, JENSEN'S ALPHA DAN SORTINO - , Linawati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mutual fund (Reksa Dana) can be used as one of the investment alternatives besides personal saving, time deposit, shares and bond. Mutual fund is an investment that has a form as a collective contract investment and managed by professionals. From various kind of mutual funds in Indonesia, investors have to choose which mutual fund that can give them optimal return. The problem is which type of indicators that can be used by investors to help them choosing the mutual fund. The writer did research with 6 equitybased mutual funds in Indonesia with the period from December 31, 2006 to December 31, 2010. Firstly, the writer measures the performance of all the equity-based mutual funds based on raw return, Sharpe, Treynor, Jensenâs Alpha and Sortino method then compare them with the performance of the benchmark (IHSG). The ones (mutual fund) that can beat the IHSG is considered as superior, and vice versa the ones that canât beat IHSG considered as inferior. Afterwards, whether there is any consistency in the performance is checked by using probabilistic method. Then, ranking will be made started with the best to the worst equity-based mutual funds. The best mutual fund is the ones that achieve the most superior position based on the 5 methods above. Here are the equity-based mutual funds that can achieve superior position every year during the research period: Bahana Dana Prima, Danareksa Mawar, Panin Dana Maksima dan Phinisi Dana Saham.